ANALYSIS ON THE IMPACT OF ORGANIZATIONAL CULTURE AND JOB SATISFACTION TOWARDS EMPLOYEE TURNOVER INTENTION (A CASE STUDY OF BANK XYZ) - Kharismawan, Fariz Prasetya; Sucento, Bun (APPS Publications, 2019)
The purpose of this study is to analyze the impact of organizational culture and job satisfaction towards employee turnover intention. The method used in this study is using quantitative method. Primary data were obtained by distributing printed questionnaires to 70 employees of Bank XYZ in Jakarta. The result of this study identified the impact of innovation and risk taking, people orientation, also team orientation as the characteristics of organizational culture with benefit and compensation, relation with co-worker and opportunity for promotion as the characteristics of job satisfaction toward employee turnover intention. The company can get insight for improving its organizational culture and job satisfaction to reduce the number of employee turnover intention.